"Records of Simple Truth and Precision": Photography, Archives, and the Illusion of Control - Schwartz, Joan M. (Archivaria, 2000)
This introduction to early nineteenth-century critical writing on photog-raphy as a constellation of technologically, culturally, and socially constructed practices prompts reflection upon the shared paradigmatic origins of photographic practices and archival practices. In elucidating the role of photographs in the production of social knowledge, it also furnishes insights into the function of photographs in society– in the business of life and in the life of business – and, by extension, sheds newlight on the nature of photographs as documents and the place of photographs inarchives. Finally, it invites close consideration of the parallels between the vocabularies of photography and archives, and of the implications of the postmodern destabilization of photographic truth on the intellectual underpinnings of archives. RÉSUMÉ Cette introduction à la littérature critique du début du XIXe siècle sur laphotographie, vue comme une constellation de pratiques technologiquement, culturellement et socialement construites, amène l’auteure à une réflexion sur les origines paradigmatiques communes des pratiques photographiques et archivistiques. Enéclairant le rôle des photographies dans la production de la connaissance sociale, ellefournit également des idées sur la fonction des photographies dans la société – dansles affaires de la vie ou dans la vie des affaires – et, par extension, répand unenouvelle lumière sur la nature des photographies en tant que documents et sur la placede celles-ci dans les archives. Finalement, elle invite à prendre en considérationles parallèles entre les vocabulaires de la photographie et des archives, ainsi que lesimplications de la déstabilisation post-moderne de la vérité photographique sur lesfondements intellectuels des archives.